Cultivation of colored fiber cotton ’BRS Jady’ with saline water and organic fertilization - Souza, Leandro de Pádua; Fatima, Reynaldo Teodoro de; Lacerda, Cassiano Nogueira de; Soares, Lauriane Almeida dos Anjos; Silva, André Alisson Rodrigues da; Veloso, Luana Lucas de Sá Almeida (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The use of saline waters in agriculture has become an alternative for the expansion of irrigated agriculture in the semiarid regions. However, it is necessary to develop techniques capable of mitigating the effects of stress caused by excess salts on plants. In this context, the objective of present study was to evaluate the growth and production of cotton cv. BRS Jady irrigated with waters of increasing levels of salinities and doses of organic fertilization. The experiment was conducted using a Regolith Neosol of a sandy-loamy texture in a greenhouse in the municipality of Campina Grande – PB. The experimental design was a randomized block design, in a 4 x 4 factorial scheme, with three replications, being the treatments composed of four levels of electrical conductivity of water (ECw, 1.7, 3.4, 5.1 and 6, 8 dS m-1) and four doses of organic fertilization (0, 2.5, 3.5 and 4.5% on the basis of soil volume). Water salinity of up to 6.8 dS m-1 reduces relative growth rates, specific leaf area, leaf area ratio and harvest index of cotton cv. BRS Jady. Organic fertilization attenuates the effects of irrigation water salts on the net assimilation rate and total dry mass of cotton cv. BRS Jady, with a dose of 4.5% MO showing the best results.